The Relationships Between Self-Discipline and Peer-Groups With Smoking Behavior in High School Students - Muhamad Uyun; Fitriani Sudirman (Psikostudia : Jurnal Psikologi, 2022)
One form of negative human behaviour is smoking behaviour. According to re-searchers, two (2) factors influence smoking behavior: self-discipline and peer groups with smoking behaviour. The purpose of this study is to know the correlation between self-discipline and peers-groups with smoking behavior. Correlational quantitative research method, with data collection technique using a scale of, population and sample of high school students in Palembang.The analyt-ical technique used to test the hypothesis is multiple regression with a simple random sampling technique. The analysis results prove that for the minor hypoth-esis, there is a significant negative relationship between self-discipline variables and smoking behavior (r=-0.541; F=53,741; (p<0.01). The results of the second mi-nor hypothesis prove that there is a significant positive relationship between peer groups variables and behavior. Smoking (r=0.469; F=36,639; (p<0.01). Then, the major hypothesis results indicate a significant negative relationship between self-discipline and peer groups with smoking behaviour (r=-0.662; F=50.349; (p<0.01). In conclusion, all the hypotheses put forward are proven, the implications for school and teachers are to apply stringent rules and discipline in terms of smoking behaviour. Salah satu bentuk perilaku negatif manusia adalah perilaku merokok. Menurut pencari ulang, dua (2) faktor yang mempengaruhi perilaku merokok: disiplin diri dan kelompok sebaya dengan perilaku merokok. Tujuan dari penelitian ini adalah untuk mengetahui korelasi antara disiplin diri dengan peers-group dengan perilaku merokok. Metode penelitian kuantitatif korelasional, dengan teknik pengumpulan data menggunakan skala, populasi dan sampel siswa SMA di Palembang.Teknik analitik-ical yang digunakan untuk menguji hipotesis adalah regresi berganda dengan teknik random sampling sederhana. Hasil analisis membuktikan bahwa untuk hipoth-esis minor, ada hubungan negatif yang signifikan antara variabel disiplin diri dan perilaku merokok (r=-0.541; F=53.741; (hlm<0,01). Hasil hipotesis mi-nor kedua membuktikan bahwa ada hubungan positif yang signifikan antara variabel dan perilaku kelompok sebaya. Merokok (r=0,469; F=36.639; (hlm<0,01). Kemudian, hasil hipotesis utama menunjukkan hubungan negatif yang signifikan antara disiplin diri dan kelompok sebaya dengan perilaku merokok (r=-0.662; F=50.349; (hlm<0,01). Kesimpulannya, semua hipotesis yang dikemukakan terbukti, implikasinya bagi sekolah dan guru adalah menerapkan aturan dan disiplin yang ketat dalam hal perilaku merokok.